The Effect of Contextual Redefinition Strategy (CRS) in Improving Students Vocabulary - Majid, Ahmad Risal; Dewi Purnama, Atmaranie (JLE: Journal of Literate of English Education Study Program, 2024)
Contextual Redefinition Strategy (CRS) is the one strategy can be used to improve vocabulary students. The aim of this research is to find the use of Contextual Redefinition (CRS) Strategy is Effective to Increase Vocabulary Achievement of the tenth grade students at MAS DDI Tellu Limpoe and to find out students’ interest toward the use of CRS strategy in improving vocabulary achievement. In the methodology of research, the researcher used mix method that applied Quantitative and Qualitative method. The data was analyzed by using t-test. The population of this research was the tenth grade at MAS DDI Tellu Limpoe. In this research there were only one class and total students only twenty-eight. So the sample was selected using total sampling technique. The Researcher used two instruments, the first instrument is vocabulary test in order to find and know students’ vocabularies achievement and the second instrument is questionnaire to express the students’ interest in use of CR strategy in learning English vocabulary. Based on the result of t-test show that the t-test value (14.051) was higher than t-table value (2.056). From the data shows that the alternative hypothesis (Ha) is accepted and Ho is rejected. It’s means that there is a significant difference before and after teaching vocabulary through contextual redefinition strategy and using Contextual Redefinition Strategy is effective to improve students’ vocabulary achievement of Tenth Grade Students at MAS DDI Tellu Limpoe.